A novel chemically defined medium for the biotechnological and biomedical exploitation of the cell factory Leishmania tarentolae - Giulia Maria Cattaneo; Ilaria Varotto-Boccazzi; Riccardo Molteni; Federico Ronchetti; Paolo Gabrieli; Jairo Alfonso Mendoza-Roldan; Domenico Otranto; Emanuele Montomoli; Claudio Bandi; Sara Epis (Scientific Reports, 2024)
Abstract The development of media for cell culture is a major issue in the biopharmaceutical industry, for the production of therapeutics, immune-modulating molecules and protein antigens. Chemically defined media offer several advantages, as they are free of animal-derived components and guarantee high purity and a consistency in their composition. Microorganisms of the genus Leishmania represent a promising cellular platform for production of recombinant proteins, but their maintenance requires supplements of animal origin, such as hemin and fetal bovine serum. In the present study, three chemically defined media were assayed for culturing Leishmania tarentolae, using both a wild-type strain and a strain engineered to produce a viral antigen. Among the three media, Schneider's Drosophila Medium supplemented with Horseradish Peroxidase proved to be effective for the maintenance of L. tarentolae promastigotes, also allowing the heterologous protein production by the engineered strain. Finally, the engineered strain was maintained in culture up to the 12th week without antibiotic, revealing its capability to produce the recombinant protein in the absence of selective pressure.